2011
DOI: 10.1002/pmic.201100173
|View full text |Cite
|
Sign up to set email alerts
|

Gel‐based phosphoproteomics analysis of sarcoplasmic proteins in postmortem porcine muscle with pH decline rate and time differences

Abstract: Meat quality development is highly influenced by the pH decline caused by the postmortem (PM) glycolysis. Protein phosphorylation is an important mechanism in regulating the activity of glycometabolic enzymes. Here, a gel-based phosphoproteomic study was performed to analyze the protein phosphorylation in sarcoplasmic proteins from three groups of pigs with different pH decline rates from PM 1 to 24 h. Globally, the fast pH decline group had the highest phosphorylation level at PM 1 h, but lowest at 24 h, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 39 publications
2
82
0
Order By: Relevance
“…In 514 particular, phosphoproteomic analysis of sarcoplasmic proteins in post-mortem porcine 515 muscle revealed high levels of phosphorylation in stress response proteins [55]. We 516 found that two phosphorylated fast skeletal myosin light chain 2 isoforms (i.e.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 83%
See 1 more Smart Citation
“…In 514 particular, phosphoproteomic analysis of sarcoplasmic proteins in post-mortem porcine 515 muscle revealed high levels of phosphorylation in stress response proteins [55]. We 516 found that two phosphorylated fast skeletal myosin light chain 2 isoforms (i.e.…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 83%
“…It should also be highlighted that increased levels of pH in 527 DFD compared to normal meat may run against the activity of acid phosphatases [55]. 528…”
Section: Tof/tof Ms (Supplementarymentioning
confidence: 99%
“…Examples include post-mortem protein degradation [77,78], increased level of oxidation [79,80] and phosphorylation [36,67] of specific muscle proteins during post-mortem storage. Therefore, whether post-mortem changes have a role in reducing the abundance and/or confound the identification of these proteins may require further study.…”
Section: Fig 3 -Number Of Proteins Identified In the Three Crude Framentioning
confidence: 99%
“…Protein maps or catalogues of the skeletal muscle have been generated for several vertebrate species such as human [30,31], cattle [32][33][34], pigs [35,36], rabbits [37,38], mice [39][40][41][42] and cod [43]. In this study, we aimed to characterise the proteome of lamb meat derived from longissimus lumborum muscle.…”
Section: Introductionmentioning
confidence: 99%
“…These data strongly argue that activated AMPK, possibly through modulation of phosphofructokinase 1 and 2 activities-the latter catalyses the production of fructose 2,6-bisphosphate and increases PFK1 activity-may impact post-mortem metabolism and subsequent meat quality development. Others supported this notion by showing that global phosphorylation patterns, possibly through AMPKmediated events or otherwise, occur post-mortem and may alter the transformation of muscle to meat (Huang et al 2011;Lametsch et al 2011).…”
Section: Glycolysismentioning
confidence: 99%